Bird's new shoes - Riddell, Chris (New York : H. Holt, 1987)
Rat, Goat, Snake, and other animal acquaintances get into an argumentative frenzy over what is the latest fashion in clothing.
Keywords: Fashion -- Fiction; Clothing and dress -- Fiction; Animals -- Fiction